2010
DOI: 10.5051/jpis.2010.40.1.19
|View full text |Cite
|
Sign up to set email alerts
|

A clinical study of alveolar bone quality using the fractal dimension and the implant stability quotient

Abstract: PurposeIt has been suggested that primary implant stability plays an essential role in successful osseointegration. Resonance frequency analysis (RFA) is widely used to measure the initial stability of implants because it provides superior reproducibility and non-invasiveness. The purpose of this study is to investigate whether the fractal dimension from the panoramic radiograph is related to the primary stability of the implant as represented by RFA.MethodsThis study included 22 patients who underwent dental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
64
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(67 citation statements)
references
References 24 publications
3
64
0
Order By: Relevance
“…In recent studies, it was reported that RFA was a reliable tool for assessment of implant stability and ISQ value significantly correlated with other implant stability parameters such as insertion torque value, bone density, actual micro‐motion value, and fractal analysis . However, controversial results were also reported about the reliability of ISQ for the assessment of implant stability .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent studies, it was reported that RFA was a reliable tool for assessment of implant stability and ISQ value significantly correlated with other implant stability parameters such as insertion torque value, bone density, actual micro‐motion value, and fractal analysis . However, controversial results were also reported about the reliability of ISQ for the assessment of implant stability .…”
Section: Discussionmentioning
confidence: 99%
“…32,33 In this study, we used In recent studies, it was reported that RFA was a reliable tool for assessment of implant stability and ISQ value significantly correlated with other implant stability parameters such as insertion torque value, 11,19 bone density, 11,21 actual micro-motion value, 34 and fractal analysis. 35,36 However, controversial results were also reported about the reliability of ISQ for the assessment of implant stability. 37,38 Some factors can affect implant stability and ISQ recordings such as bone quality, shape of the implant, thread design, surface treatment, surgical technique and the experience of the surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…FD on periapical radiographs has been used as an identifier of the complex pattern of the alveolar bone surrounding the dentition 7 . The potential of fractal analysis, which has been proven to be independent of projection geometry, 9 has been found in numerous applications in several branches of dental practice related to the evaluation of the trabecular bone 10‐12 …”
mentioning
confidence: 99%
“…7 The potential of fractal analysis, which has been proven to be independent of projection geometry, 9 has been found in numerous applications in several branches of dental practice related to the evaluation of the trabecular bone. [10][11][12] Many signs and symptoms of periodontitis can be diagnosed both clinically and with radiographs. However, no diagnostic method is currently available to demonstrate the initial stages of transition from gingivitis to periodontitis.…”
mentioning
confidence: 99%
“…They found no correlation amongst them. However Lee et al [18], found a correlation between FD and the implant stability quotient (ISQ), the main output parameter from an Osstell TM device.…”
Section: Dental Implantsmentioning
confidence: 98%